PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE - Prasetya, Gustivo; Muid, Dul (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of profitability (ROA) and leverage (DER) on tax avoidance (Y). The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sample of this study used a non-probability sampling method with a purposive sampling technique. The data analysis technique used the classical assumption test, namely the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. Hypothesis testing using multiple regression analysis. The results of the study conclude that: (1) Profitability has a positive effect on Tax Avoidance, (2) Leverage has a positive effect on Tax Avoidance.